디자인씽킹을 적용한 성폭력예방 기능성 게임 - 정혜인(Hea-In Jung); 양용철(Yong-Chil Yang) (디지털콘텐츠학회논문지, 2017)
이 연구는 교사들을 위한 성폭력예방교육을 대체할 기능성 게임을 제작하는 과정에서 게임의 콘텐츠 개발을 위한 사전 작업으로 진행되었다. 대상자의 분석과 새로운 교육서비스로 성폭력예방 기능성 게임의 활용을 제안하는 데 있다. 이를 위해서 디자인씽킹의 방법론에서 고든기법과 서비스 블푸프린트 기법이 적용되었다. 대상자 분석에서 나온 결과는 기능성 게임의 목적에 부합하는 요소와 재미 및 지속적인 교육이 되도록 하는 것이었다. 또한, 성폭력예방교육과 함께 기능성게임 참여자에게 교육이수 확인도 제안되었다. This study was conducted with preliminary to develop the game contents for designing of sexual violence prevention serious game for school teachers. It is proposed to use of sexual violence prevention serious game with the analysis of the audience and a new approach. For this purpose, Gordon method and Service Blueprint method were applied in design thinking. The results from analyzing the audiences were to reflect the components of corresponding with the goal of the serious game, and interest and motivation for continuing education. Also, it was proposed to give the certificate of education participation to teachers attended in the serious game in-service education. KCI Citation Count: 1